2019
DOI: 10.11591/ijeecs.v14.i2.pp903-911
|View full text |Cite
|
Sign up to set email alerts
|

A simplify fuzzy logic controller design based safe experimentation dynamics for pantograph-catenary system

Abstract: Contact force between catenary and pantograph of high speed train is a crucial system to deliver power to the train. The inconsistence force between them can cause the contact wire oscillate a lot and it can damage the mechanical structure of system and produce electric arc that can reduce the performance of system. This project proposes a single-input fuzzy logic controller (SIFLC) to control the contact force between the pantograph-catenary by implement Safe Experimentation Dynamics (SED) method to tune the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Each player moves in a random motion that is decided based on a predetermined probability. Since its first debut, SEDA has been utilized as a tool to cater to various engineering applications such as flexible joint robots [52], pantograph-catenary systems [53], underactuated container cranes [54], and DC/DC buck-boost converter-inverter-DC motors [55]. In the domain of a single agent, systematic studies have shown that SEDA has solid performance and is very simple to implement, with a safe updating mechanism.…”
Section: Hybridization Of Mpa and Sedamentioning
confidence: 99%
“…Each player moves in a random motion that is decided based on a predetermined probability. Since its first debut, SEDA has been utilized as a tool to cater to various engineering applications such as flexible joint robots [52], pantograph-catenary systems [53], underactuated container cranes [54], and DC/DC buck-boost converter-inverter-DC motors [55]. In the domain of a single agent, systematic studies have shown that SEDA has solid performance and is very simple to implement, with a safe updating mechanism.…”
Section: Hybridization Of Mpa and Sedamentioning
confidence: 99%
“…This manuscript proposes a model-free single-dimension fuzzy-based sliding mode control (SDF-SMC) design. The technique of single-dimension fuzzy-based sliding mode control has been proposed previously without model-free approach for several applications such as deep submergence rescue vehicle (DSRV) [41], double pendulum-type overhead crane [42] and NPS AUV II [43] for Pantograph-Cateary system [44] and for underactuated quadrotor craft [45]. This algorithm produced many methods, such as fast convergence rate, prompt execution time response, less chattering effect and less control input energy (CIE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper discusses the integrated application of synergetic approach to improve the quality of intelligent steam generator control system. This approach combines various aspects and techniques including model-based control, adaptive control and artificial intelligence to create an efficient and flexible steam generator control system [3]- [5]. Model-based control provides a mathematical model of the steam generator, which is used to develop control algorithms and predict its behavior.…”
Section: Introductionmentioning
confidence: 99%